Adaptations during the acquisition of expertise - Gruber, H.; Jansen, P.; Marienhagen, J.; Altenmueller, E. (Talent Development & Excellence, 2010)
For a long period, outstanding performance in complex domains was explained by innate abilities. Research on expertise questioned this assumption and showed that performance can tremendously be influenced by intensive deliberate practice. Evidence about the plasticity of the human mind and body suggests that the acquisition of expertise should rather be described as process of specific adaptations to typical tasks of the domain rather than as development of pre-existing innate abilities. Cognitive adaptations have been addressed in research on expertise for nearly half a century, whereas the investigation of physiological and neural adaptations as result of deliberate practice in specific domains is still at its beginning. Recent developments in sciences like neuroscience, training and exercise theory, physiology, or neurology, open new theoretical and technical possibilities to investigate such adaptations. Neuroimaging methods allow empirical analyses of functional and structural (anatomical) changes of the brain as result of intensive domain-specific practice. In this article, recent research concerning motor, physiological and neural plasticity is reviewed. Considerations are suggested how such research might influence educational issues of supporting the acquisition of expertise.